Lessons Learned From the Battlefield and Applicability to Veterinary Medicine—Part 1: Hemorrhage Control - Edwards, Thomas H.; Dubick, Michael A.; Palmer, Lee; Pusateri, Anthony E. (Frontiers in Veterinary Science, 2021)
In humans, the leading cause of preventable death on the modern battlefield is undoubtedly exsanguination from massive hemorrhage. The US military and allied nations have devoted enormous effort to combat hemorrhagic shock and massive hemorrhage. This has yielded numerous advances designed to stop bleeding and save lives. The development of extremity, junctional and truncal tourniquets applied by first responders have saved countless lives both on the battlefield and in civilian settings. Additional devices such as resuscitative endovascular balloon occlusion of the aorta (REBOA) and intraperitoneal hemostatic foams show great promise to address control the most difficult forms (non-compressible) of hemorrhage. The development of next generation hemostatic dressings has reduced bleeding both in the prehospital setting as well as in the operating room. Furthermore, the research and fielding of antifibrinolytics such as tranexamic acid have shown incredible promise to ameliorate the effects of acute traumatic coagulopathy which has led to significant morbidity and mortality in service members. Advances from lessons learned on the battlefield have numerous potential parallels in veterinary medicine and these lessons are ripe for translation to veterinary medicine.